The Coining of Convivial Public Space: Homelessness, Outreach Work, and Interaction Order - Robin James Smith; Jonathan Ablitt; Joe Williams; Tom Hall (Urban Planning, 2023)
This article engages with the “convivial turn” in writings about the city and offers a reorientation of sorts. Beginning with encounters, rather than particular spaces, we make the case that conviviality and its limits are realised in practices. Rather than starting in set piece urban spaces designed to foster conviviality we start out on the move, with frontline street-based care and outreach workers in Cardiff, Wales, and Manhattan, New York City, as they seek out and meet up with those sleeping on city streets. This provides a view of an improvised conviviality that makes the most of whatever the material affordances of a given city space happen to provide. Our research points to how these encounters necessarily take place in marginal settings and times due to the sorts of exclusions that can be built into contemporary city spaces that can at the same time be welcoming to the public, but hostile toward those most in need and vulnerably located in the centre of things. In this sense, we approach conviviality as a fragile interactional accomplishment and, in doing so, see questions of conviviality and conflict as less of a big-picture paradox of togetherness and distance, hope and hate in urban life, and more of a dynamic relation of co-presence and visibility. Public space, and indeed public life, might then be reconsidered not as a location but, rather, an active, shifting accomplishment, variously coloured by the politics of seeing and being seen.